Mothers' Knowledge, Attitudes, and Support from Health Workers Influencing The Maternal and Child Health (MCH) Handbook Utilization for Maternal and Child Health in Palembang - Kumalasari, Intan (Chakra Brahmanda Lentera Institute, 2024)
Background: The Maternal and Child Health (MCH) Handbook is an essential tool in improving the health of pregnant women and young children. Serving as both a medical record and an educational resource, it provides vital health information for mothers and children. However, the utilization and understanding of the MCH Handbook vary across regions. This study evaluates the use of the MCH Handbook in monitoring maternal and child health in Palembang City. Methods: A quantitative cross-sectional design was employed, targeting pregnant women and mothers with children aged 0–5 years from eight health centers in Palembang City. A total of 240 respondents were selected using simple random sampling. Data collection instruments were validated for reliability through Spearman-Brown, Guilford, and Cronbach's Alpha methods. Statistical analyses explored associations between utilization and factors influencing MCH Handbook use. Results: The findings indicate a high utilization rate of the MCH Handbook in Palembang City (84.2%), though variations exist in its frequency and quality of use. Key factors influencing utilization include mothers' knowledge (p=0.042, OR 2.050), attitudes (p=0.000, OR 6.718), and health worker support (p=0.000, OR 21.44). Mothers who actively use the MCH Handbook demonstrate better knowledge and attitudes toward health care during pregnancy and early childhood. Health worker support significantly enhances usage, with supported mothers being 21.44 times more likely to utilize the handbook effectively. Conclusion: In conclusion, the MCH Handbook significantly contributes to improving maternal and child health. Strengthened socialization programs, targeted training for mothers, and ongoing health worker support are recommended to optimize its utilization and effectiveness.